Barriers to effective communication among nurses and family members of patients admitted to the intensive care unit at Muhimbili National Hospital in Dar es Salaam: A descriptive qualitative study - Menti Lastone Ndile; Scholastica Charles; Gift Lukumay (PLoS ONE, 2025)
Background Effective communication in healthcare is essential for ensuring quality patient care. As healthcare shifts toward family-centered care, nurses are expected to engage families in information sharing and decision-making about their patients. However, barriers to effective communication in intensive care units (ICUs) exist. While global studies have addressed nurse-family communication, most are quantitative and conducted in contexts not similar to Tanzania. This study aimed to qualitatively explore the barriers nurses face in the Tanzanian context when communicating with family members in the ICUs at Muhimbili National Hospital, Dar es Salaam, Tanzania. Methods A descriptive qualitative study was conducted using semi-structured interviews to explore communication barriers. Purposive sampling was used to select fifteen ICU nurses and twelve family members of ICU patients at Muhimbili National Hospital. All interviews were audio-recorded with consent and transcribed verbatim. Data were analyzed thematically following Braun and Clarke’s six-phase framework. Results The study identified two main themes emerging from the interviews: 1) Interpersonal barriers affecting the nurse-family relationship, and 2) Organizational barriers related to the work environment and resource limitations. Conclusion The study highlights that improving communication in ICU settings goes beyond individual efforts; it requires investment in staff training, adequate infrastructure, and a supportive organizational culture. Addressing both interpersonal and organizational barriers through targeted interventions can foster trust, enhance family satisfaction, and contribute to improved patient outcomes in critical care environments.